STCM: Secured trust-based communication method in vulnerable mobile adhoc network - Khan, Burhan Ul Islam; Olanrewaju, Rashidah Funke; Baba, Asifa Mehraj; Zulkurnain, Nurul Fariza; Lone, Sajad Ahmad (Springer, 2017)
Mobile Adhoc network is shrouded with various issues where majority of the problems encircle around routing and security issues. The root cause of such unsolved issues is dynamic topology and decentralized architecture. A closer look into the existing literatures shows that cryptography is the frequently used technique to ensure security in communication of mobile Adhoc network; however, there are associated issues with cryptographic implementation in security. Hence, this paper introduces a scheme based on trust factor which is less recursive and less computationally complex scheme as compared to conventional cryptographic based approaches. The proposed system applies a novel design of control message that uses simple tree to maintain certiﬁcates and performs authentication of nodes based on trust factor of node with respect to identity and behavioral pattern of the mobile nodes. The outcome of the study shows better security and communication performance in comparison to frequently used routing approaches.